All Days 2014
DOI: 10.2118/172448-ms
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of Nanomaterials in Enhanced Oil Recovery

Abstract: Given the large amount of by-passed oil and gas and low oil recovery factors in many reservoirs coupled with global energy demand projected to rise as high as almost 60%in the next 30 years particularly in Africa, it is quite evident that convectional petroleum engineering techniques are not adequate and efficient for reservoir characterization and production optimization. This challenging trend may be met only by revolutionary breakthroughs in energy science and technology. The industry thus requires stunning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Nanotechnology has had gigantic impact in nearly every industry from consumer electronics to healthcare and telecommunication [15]. Nanotechnology has also been applied in the oil and gas industry, such as in Enhanced Oil Recovery Technology, but however has had relatively limited application in the field [15].…”
Section: Factors Which Affect Permeability Declinementioning
confidence: 99%
See 2 more Smart Citations
“…Nanotechnology has had gigantic impact in nearly every industry from consumer electronics to healthcare and telecommunication [15]. Nanotechnology has also been applied in the oil and gas industry, such as in Enhanced Oil Recovery Technology, but however has had relatively limited application in the field [15].…”
Section: Factors Which Affect Permeability Declinementioning
confidence: 99%
“…From a lab test, [15] test showed that small concentrations of nanoparticles can increase the viscosity of water-based fluids without reasonably affecting their densities and could provide potential enhancement in the efficiency of oil recovery. According to [15], the surface environment is generally incompatible with the stability envelope of a lot of nanoparticles. Protective or active layers can be fabricated around the particles in order to shield them from high temperature, pressure and unfavourable chemicals that are in the reservoir.…”
Section: Factors Which Affect Permeability Declinementioning
confidence: 99%
See 1 more Smart Citation
“…The nanofluids technique has the potential to further increase production over traditional chemical EOR, and also in enhancing the injection effect, which has gained worldwide attentions. [21,[38][39][40][41] Capillary number, reservoir surface wettability, and nanomaterial properties are factors to be considered in nanofluids technique. Using molecular dynamics simulation, Miranda et al [42] studied the effect of reservoir surface wettability and nanofluid diffusion behaviour at the molecular level, and also examined the stability and mobility of functionalized silica nanoparticles.…”
Section: Enhanced/improved Oil Recovery (Eor/ior)mentioning
confidence: 99%